18.4k views
2 votes
The solution to the system shown in the graph is

Select one:
a. (2,3)
b. (4,0)
c. (3,2)
d. (0,6)
y=-1.5x+6

y=x+1

2 Answers

7 votes

Answer: a. (2,3)

Step-by-step explanation: y=-1.5x+6--(1)

y=x+1--(2)

Sub y=x+1 into (1)

x+1=-1.5x+6

2.5x=5

x=2

Sub x=2 into (2)

y=3

User Andrey Marchuk
by
4.8k points
3 votes

a. (2,3)

Answer:

Solution Given:

y= -1.5x+6........[1]

y=x+1.................[2]

Now solving equation 1 and 2 we get

-1.5x+6=x+1

6-1=x+1.5x

2.5x=5

x=5/2.5

x=2

again

substituting value of x in equation 2, we get

y=2+1=3

so

solution(x,y)=(2,3)

Explanation:

User Pierrette
by
5.4k points